Vengeance : the last stands of Custer, Crazy Horse, and Sitting Bull - Clavin, Tom, 1954- (St. Martin's Press, 2026)
"A dramatic new look at Custer's Last Stand in time for the 150th anniversary of the Battle of the Little Bighorn, by the #1 New York Times bestselling coauthor of The Heart of Everything That Is. On June 25-27, 1876, the Battle of the Little Bighorn, commonly referred to as Custer's Last Stand, was fought between combined forces of the Lakota Sioux, Northern Cheyenne, and Arapaho tribes and the 7th Cavalry Regiment of the United States Army. Along the Little Bighorn River in Montana Territory, the battle resulted in the devastating defeat of U.S. forces and was the most significant action of the Great Sioux War of 1876. This dramatic look at the Little Bighorn battle includes not only the Native American point of view-with two dynamic Native figures, Sitting Bull and Crazy Horse, on prominent display-but also the impact it had on the Plains Indians. It turned out to be their last stand too because a vengeful nation quashed any remaining resistance, with a conclusive massacre at Wounded Knee in 1890, almost simultaneous with the murder of Sitting Bull. In addition, Custer's character by June 1876 is at the heart of this world-famous disaster. For all his celebrated bravery, especially at Gettysburg 13 years earlier, Custer became a devout media hound, desperate to gain fame. Even, some say, his own demise was a misguided attempt at grabbing national headlines: He envisioned a massacre - just not his own. As both the camera and the tabloid came of age, George Armstrong Custer became America's first bona fide celebrity. Vengeance is a thrilling read, filled with action, legendary characters, and poignance for the impact this had on Native Americans and the shape of the American West"-- Provided by publisher.